Design and control three phase AC to DC converter for grid connected applications - Muhammad Shahril, Siti Hanum (2018)
The problem in transmission and distribution lines due to the harmonic and reactive current injected to the grid system by line commutated power diode and thyristor rectifiers has triggered the vast development in power electronic devices since the last decade. The three phase ac-dc converters with the proper control strategies have gained more interest in medium and high voltage applications because of their various benefits such as nearly sinusoidal input current, reduce harmonic in the line current, and operate near to unity power factor. In this dissertation, the voltage oriented control is applied through the usage of the outer voltage control loop and inner current control loop which is can improved the performance of the converter among the other control technique. The proposed system is designed and analysed using MATLAB/Simulink software. Various performances results from the simulation of proposed ac-dc converter have been investigated. Based on the analysis from the simulation results, it has been found that the proposed VOC is able to produce three phase sinusoidal input current with low total harmonic distortion, near unity power factor and adjustable de-link output voltage under balanced, unbalanced and distorted input voltage supply.